Global desertification vulnerability to climate change and human activities - Huang, Jianping; Zhang, Guolong; Zhang, Yanting; Guan, Xiaodan; Wei, Yun; Guo, Ruixia (Land degradation & development, 2020)
Desertification is the impoverishment of arid, semiarid, and some subhumid ecosystems. The assessment of global scale desertification vulnerability to climate change and human activity is important to help decision makers formulate the best strategies for land rehabilitation and combat global desertification in sensitive areas. There is no global desertification vulnerability map that considers both climate change and human activities. The main aim of this study was to construct a new index, the global desertification vulnerability index (GDVI), by combining climate change and human activity, provide another perspective on desertification vulnerability on a global scale, and project its future evolution. Using the probability density function of the GDVI, we classified desertification vulnerability into four classes: very high, high, medium, and low. The results of the analysis indicated that areas around deserts and barren land have a higher risk of desertification. Areas with a moderate, high, and very high desertification risk accounted for 13%, 7%, and 9% of the global area, respectively. Among the representative concentration pathways (RCPs), RCP8.5 projected that the area of moderate to very high desertification risk will increase by 23% by the end of this century. The areas where desertification risks are predicted to increase over time are mainly in Africa, North America, and the northern areas of China and India.